2018
DOI: 10.3390/buildings8040059
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Environmental Perspectives among Urban Design Professionals

Abstract: Urban design professionals are key actors in early design phases and have the possibility to influence urban development and direct it in a more sustainable direction. Therefore, gender differences in environmental perspectives among urban design professionals may have a marked effect on urban development and the environment. This study identified gender differences in environment-related attitudes among urban design professionals involved in the international architectural competition 'A New City Centre for K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
3
12
1
Order By: Relevance
“…Since the origin of environmental behavior literature, there has been much observational evidence to suggest that women are more worried about the environment than men, and that this is reflected in their greater levels of proenvironmental behavior (e.g., Stern et al, 1993;Davidson and Freudenburg, 1996;Ramstetter and Habersack, 2019). However, females in our study self-rated their own environmental behavior as lower (i.e., less environmentally friendly) than men -which would be counter to the observational evidence (e.g., Lam and Cheng, 2002;Wallhagen et al, 2018). Given that our study was not specifically designed to test for such gender differences we do not have adequate evidence to explain these findings, however, we posit that females may under-report the adequacy of their own behavior for gender related reasons.…”
Section: Discussioncontrasting
confidence: 80%
“…Since the origin of environmental behavior literature, there has been much observational evidence to suggest that women are more worried about the environment than men, and that this is reflected in their greater levels of proenvironmental behavior (e.g., Stern et al, 1993;Davidson and Freudenburg, 1996;Ramstetter and Habersack, 2019). However, females in our study self-rated their own environmental behavior as lower (i.e., less environmentally friendly) than men -which would be counter to the observational evidence (e.g., Lam and Cheng, 2002;Wallhagen et al, 2018). Given that our study was not specifically designed to test for such gender differences we do not have adequate evidence to explain these findings, however, we posit that females may under-report the adequacy of their own behavior for gender related reasons.…”
Section: Discussioncontrasting
confidence: 80%
“…Females show a significantly higher RV score than males, even if the effect according to the common interpretation [ 90 ] is small (d = .273). It is reported that females consider environmental aspects to be more important [ 91 ]. Zhang et al [ 69 ] discovered that females are more connected to nature and appreciate the beauty of nature more.…”
Section: Discussionmentioning
confidence: 99%
“…This positions architecture as an anomaly of women's progression at student level and beyond (Sánchez De Madariaga, 2010). With multidisciplinary collaboration as an accepted requirement of the architectural skillset (Wallhagen et al , 2018), there are also negative findings on the workplace experience of women when liaising with other professions. On-site consultant liaison, particularly in areas of construction, becomes a major disconnect where gender bias is exasperated by stereotypical perceptions (Lim et al, 2018; Pickerill, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The attrition of women in the workforce is a well-established topic across various professions, where long-term retention often serves as an indicator of progressive societal change. This issue is further exacerbated in more male-dominated workforces, or workforces that are perceived as such, including for example, engineering, medicine and architecture (Goris, 2020; Lim et al , 2018; Smitheram et al , 2012; Wallhagen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%